Veillonella parvula Discitis and Secondary Bacteremia: a Rare Infection Complicating Endoscopy and Colonoscopy? - Marriott, D. (American Society for Microbiology, 2007)
We report a case of Veillonella parvula lumbar discitis and secondary bacteremia confirmed by molecular characterization of the 16S rRNA genes. Identification of the organism was essential for an appropriate choice of antimicrobial therapy following the failure of empirical flucloxacillin. Veillonella spp. are normal flora of the gastrointestinal tract, raising the possibility that an endoscopy and colonoscopy performed 8 weeks prior to presentation, during which small intestinal and rectal biopsies were obtained, was the portal of entry. This case highlights the importance of obtaining a microbiologic diagnosis, particularly in patients who previously have had procedures involving instrumentation.